2004
DOI: 10.1530/eje.0.1500643
|View full text |Cite
|
Sign up to set email alerts
|

A meiotic recombination in a new isolated familial somatotropinoma kindred

Abstract: We report here the genetic findings of a new isolated familial somatotropinoma (IFS) kindred in which the mother (subject I:2) and one daughter (subject II:2) are affected; their ages at diagnosis were 25 and 14 years respectively. Additionally, patient I:2 developed virilization due to an androgen-secreting adrenocortical mass, presenting clinical and molecular features of sporadic adrenal carcinoma. To genotype this family and to narrow down the candidate interval of the putative IFS gene at 11q13, we perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 36 publications
(20 reference statements)
0
18
0
1
Order By: Relevance
“…No relevant family history of MEN1-like features was seen and limited family screening (one brother) was negative. Despite the MEN1-like features of the patients described, studies from Ozawa and colleagues at the NIH and from (24). Despite the advent of mutations in AIP as potential causative features in IFS, the genetic pathophysiology of IFS remains to be fully described as we have found that in 50% of IFS families, no AIP mutations exist (25).…”
Section: Men1mentioning
confidence: 79%
“…No relevant family history of MEN1-like features was seen and limited family screening (one brother) was negative. Despite the MEN1-like features of the patients described, studies from Ozawa and colleagues at the NIH and from (24). Despite the advent of mutations in AIP as potential causative features in IFS, the genetic pathophysiology of IFS remains to be fully described as we have found that in 50% of IFS families, no AIP mutations exist (25).…”
Section: Men1mentioning
confidence: 79%
“…47 In 2004, Luccio et al narrowed the area involved in the pathogenesis of IFS. 48 In 2005, Soares et al further narrowed the area involved in the IFS. 49 In 2006, Vierimaa et al identified germline mutations (nonsense mutation Q14X in exon 1, splice site mutation IVS3-1G>A in exon 4 and a nonsense mutation R304X in exon 6) in the AIP gene in individuals with PAP.…”
Section: 12mentioning
confidence: 99%
“…Apart from the linkage of IFS to 11q13, the possibility for a linkage to 2p16 has also been raised, although data are still inconclusive [71,72,73]. Additional analysis of IFS families and tumor deletion mapping in sporadic somatotropinomas allowed the positioning of the IFS locus to be narrowed down to a 3.9-Mb area between markers D11D4908 and INT2 at 11q13 [74]. Furthermore, recent analysis narrowed the IFS locus down to a 2.21-Mb area between markers D11S4155 and D11S4136 at 11q13 (fig.…”
Section: Clinical Entities Associated With Hereditary Gh-secreting Tumentioning
confidence: 99%